Analisis Perbandingan Prilaku Konsumen Dan Minat Berbelanja Pada Pasar Tradisional Dan Pasar Modern Di Kota Langsa - Muhammad Alwi; Abdul Hamid; Shelly Midesia (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2023)
ABSTRACT The purpose of this study was to determine the differences in consumer behavior and people's buying interest when shopping at traditional markets and modern markets in Langsa City. This type of research is quantitative. The population in this study is all people who shop at traditional markets and modern markets in Langsa City whose number is unknown, while the number of samples in this study is 50 people who shop at traditional markets and 50 people who shop at modern markets. The data collection technique used is a questionnaire. Data analysis techniques in this study include research instrument testing, classical assumption test and hypothesis testing. The results showed that there were differences in consumer behavior when shopping at traditional markets and modern markets in Langsa City. This is evidenced from the results of hypothesis testing using the paired sample test, it is known that the value of consumer behavior in traditional and modern markets is obtained t arithmetic is greater than t table, which is 3.953 greater than 2.0106 and the value of sig (2-tailed) is 0.016 less than 0 0.05, then Ho is rejected and Ha is accepted and there are differences in shopping interest in traditional markets and modern markets in Langsa City. This is evidenced by the results of hypothesis testing using the paired sample test, it is known that the value of shopping interest in traditional and modern markets is obtained by t count greater than t table, which is 2.667 greater than 2.0106 and a significant value of 0.002 less than 0.05, then Ho is rejected. and Ha accepted. Keywords: Consumer Behavior, Buying Interest, Traditional Markets and Modern Markets